2021
DOI: 10.21608/edj.2021.66411.1541
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gingival Tissue Pathological Changes in Human Peri-implantitis: Histological, Immunohistochemical and Ultrastructural Study

Abstract: Aims:The current research was performed to study histopathological, immunohistochemical and ultrastructural characteristics of gingival tissue in peri-implantitis.Methods & Results: This study examined 25 patients between ages of 30-40 years. Twenty patients were selected with peri-implantitis (peri-implantitis group) in which inflamed gingival tissues were surgically removed. The gingival soft tissue collars from five healthy patients with partially impacted third molar were surgically removed (control group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, Flores et al (2021) [ 28 ] demonstrated a significant increase in type V collagen fibers in peri-implant tissues affected by peri-implantitis. Similarly, Deraz et al (2021) [ 29 ] found excessive collagenization of connective tissue in all peri-implantitis cases. Some studies argue that the peri-implant connective tissue, rather than a defense structure, is a chronic inflammatory involvement because it has many collagenase-resistant type V collagen fibers [ 9 ].…”
Section: Discussionmentioning
confidence: 85%
“…However, Flores et al (2021) [ 28 ] demonstrated a significant increase in type V collagen fibers in peri-implant tissues affected by peri-implantitis. Similarly, Deraz et al (2021) [ 29 ] found excessive collagenization of connective tissue in all peri-implantitis cases. Some studies argue that the peri-implant connective tissue, rather than a defense structure, is a chronic inflammatory involvement because it has many collagenase-resistant type V collagen fibers [ 9 ].…”
Section: Discussionmentioning
confidence: 85%